DAMPAK KECANDUAN GADGET TERHADAP EMOSI DAN PERILAKU REMAJA - Kurniawan, Vendi Eko; Anggraini, Rista Dian; Kristiana, Ike (PRIMA WIYATA HEALTH, 2025)
Background: Biological, cognitive, and socioemotional changes occur during adolescence, the time between childhood and maturity. While gadgets have many benefits, excessive use may also be detrimental. Devices are tools that can be utilized for both educational and recreational purposes. Objectives: Finding out the mental and behavioral traits of teenagers with technology addiction is the aim of this study. Methods: This study uses a descriptive quantitative research approach and a cross-sectional technique. The study's sample consisted of one hundred youths, ages thirteen to fifteen. A random selection technique was used to choose the sample of teenagers from SMPN 1 Peterongan. Descriptions were part of the data analysis for this investigation. Results: Of the answers, 57% were from men. Only a tiny minority of teenagers suffer from mental and behavioral disorders, including social challenges, emotional issues, behavioral changes, inattention, and difficulties with peer interactions, whereas 52% of them have a modest level of gadget addiction. It is feasible to conclude that adolescent gadget addiction can result in mental and behavioral issues.   Conclusion: Since parental monitoring is essential to preventing adolescents' growing addiction to electronic devices and behavioral changes, the author makes recommendations for further study that involves parents as a way to address the problem of gadget addiction in teenagers.